Visualization and Analysis of the Dynamics of Domestic and International Data Asset Research Hotspots - Wang, Song; Chen, Yijun; Gan, Yu (International Journal of Social Sciences and Public Administration, 2025)
Data assets have become an important strategic resource in the context of digital economy, and it is of great significance to improve the hot research on data assets to promote data management and application. Based on the research literature of data asset category included within CNKI and Web of Science databases between 2014 and 2023 as the data source, CiteSpace software was used for visualization and analysis. The study shows that (1) the number of domestic literature increase is slower, and the growth of foreign literature is higher than domestic. (2) The cooperation between domestic issuing institutions tends to be fragmented, and the behavior of foreign cooperative research is close and stable. (3) Domestic research hotspots focus on the background perspective of data assets, statistical accounting, and planning and management research; foreign research focuses on data application, assessment models, and performance value research.